Renewable Energy Deployment Dilemmas - Leda Žilinskienė (Bratislava Law Review, 2025)
The energy trilemma is recognised in doctrine as a means of balancing the different competing objectives of energy law and policy. The importance and weight of renewable energy in the energy trilemma is reinforced by the fact that it is a target and an important instrument in climate, sustainability and energy legislation. Despite its positive aspects, the deployment of renewable energy faces a number of obstacles, including concerns about its negative impact on the security of energy supply. It is important to develop a legal response to the controversies surrounding the deployment of renewable energy. The article aims to analyse and develop a clearer and more systematic approach to the development of renewable energy sources based on the energy trilemma. This aim was achieved using the methods of document analysis, logical-analytical, linguistic, systematic analysis. The article focuses on the analysis of scientific literature in the categories of law, as well as energy and economics, and analyses EU legislation and case law, as well as national court decisions. In the first part, a thorough literature review was carried out to explore and define the concept and objectives of the energy trilemma. The second part of the article examines the features of the relationship between renewable energy and the energy trilemma. As the understanding of the energy trilemma seems to be too general, simplistic and lacking practical applicability, the third part of the article focuses on enhancing the concept of the energy trilemma. Specific examples are used to expose internal contradictions within certain objectives of the energy trilemma, referred as renewable energy dilemmas. In general, these dilemmas have not been linked to the concept of the energy trilemma and have therefore not received sufficient attention in doctrine. The article discusses whether the energy trilemma should be used as a procedural principle of energy law. It also raises the question of whether application of the trilemma should involve the legal principle of energy solidarity.